INTERNALISASI SEMANGAT NASIONALISME MELALUI PENDEKATAN HABITUASI (Perspektif Filsafat Pendidikan) - Anwar, Chairul (Universitas Islam Negeri Raden Intan Lampung, 2014)
INTERNALIZATION OF THE SPIRIT OF NATIONALISM THROUGH HABITUATION APPROACH. (PHILOSOPHY OF EDUCATION PERSPECTIVE): Nationalism in Indonesia was born when the people of the country was under the Dutch colonial rule. This ideology appears to be a collective consciousness triggered by feelings of kinship in the past and in the time being, and more importantly, is united by the same goal for the future. In its development, however, the spirit of nationalism among the younger generation seem to weaken. This phenomenon indicates that the role of educational institutions are very important - not only to make the students understand and grasp the meaning of nationalism but also to impress them the philosophical values behind it. One way that can be taken to instill the values of nationalism is through the approach of habituation in schools, so that the values of nationalism embedded in the psyche of the student. By using the approach, teachers are believed to be able to instill the values of nationalism to their students either through routine activities, spontaneous activities, awarding exemplary activities, or, even, programmed activities.